Pengembangan Sistem Terintegrasi Real-time Monitoring dan Irigasi Cerdas pada Sawah IPB 4.0 - Supiyandi, Abi; Priandana, Karlisa; Rahmawan, Hendra (Sekolah Sains Data, Matematika, dan Informatika. Institut Pertanian Bogor, 2025)
Sawah IPB 4.0 is a smart farming concept developed by IPB University as a model for modern rice cultivation in Indonesia. This concept integrates various technologies, including real-time monitoring, smart irrigation, mechanization, smart plant protection, and multi-UAV systems. In previous studies, two core technologies—real-time monitoring and smart irrigation—were developed and implemented as Internet of Things (IoT)-based prototypes. However, these systems operated independently and lacked integrated device management capabilities. This study aims to integrate the two previously separated systems by developing a manual control module and a device management module. The system was developed using the prototyping method and implemented as a mobile application based on the Model–View–ViewModel (MVVM) architectural pattern with a single-activity architecture design. System evaluation was conducted through black-box testing to assess functionality and performance testing focused on execution time. The results of black-box testing indicate that all application features function correctly, while performance testing shows that application response times vary depending on the executed functions